2004
DOI: 10.1093/humupd/dmh018
|View full text |Cite
|
Sign up to set email alerts
|

Improving reproductive performance in overweight/obese women with effective weight management

Abstract: Obesity and overweight are common conditions in the developed countries and they carry many health consequences, including some reproductive disorders. There is a very high prevalence of obese women in the infertile population and many studies have highlighted the link between obesity and infertility. A large proportion of infertile women have polycystic ovary syndrome (PCOS) which is also linked with increased risk of obesity and other metabolic anomalies. The association between obesity and/or PCOS and hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
178
3
9

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(193 citation statements)
references
References 189 publications
3
178
3
9
Order By: Relevance
“…As a result of increasing sympathetic activity, PCOS will develop (25,26). Despite the fact that obesity and overweight are common in PCOS women (27), another finding of present study showed that the body weight in experimental group on the 60th day after EV injection, was significantly lower than control ones. Although the weight of control group was significantly increased within 60 days of study, but experimental group did not have any weight gain and instead their weight decreased slightly which was not statistically significant.…”
contrasting
confidence: 48%
See 1 more Smart Citation
“…As a result of increasing sympathetic activity, PCOS will develop (25,26). Despite the fact that obesity and overweight are common in PCOS women (27), another finding of present study showed that the body weight in experimental group on the 60th day after EV injection, was significantly lower than control ones. Although the weight of control group was significantly increased within 60 days of study, but experimental group did not have any weight gain and instead their weight decreased slightly which was not statistically significant.…”
contrasting
confidence: 48%
“…On the other hand, this result might be explained by peripheral sympathetic neuron activation after administration of a single dose of EV that may be linked to metabolic activity promotion, increased fat consumption and consequently lack of weight gain (22). However, all patients with PCOS are not overweight or obese and there are many variations in body weight among different PCOS populations (27).…”
mentioning
confidence: 99%
“…Practitioners also reported high rates of weight-loss counselling as a component of preconception care and 95% of those who undertook these discussions with overweight and obese women reported feeling comfortable engaging in this practice. This is an important component of preconception care as obesity is an independent risk factor for reduced fertility [33] and weight management interventions are effective first line treatments for infertile or subfertile obese women [34,35]. In addition, maternal obesity is associated with significant increases in complications and adverse outcomes in early pregnancy, later pregnancy, labour and the postnatal period [36].…”
Section: Discussionmentioning
confidence: 99%
“…Chance of pregnancy after bariatric surgery is increased by weight loss, which improves the ovulatory dysfunction often associated with obesity, thus increasing the risk of unplanned pregnancy if contraception is not used. 67 Nationally, approximately 50% of adolescents have engaged in sexual intercourse by age 17, however it is not clear to what extent this is true for extremely obese youth, as weight-related stigma may affect rates of sexual activity. 68 Though the weight loss associated with gastric bypass has been shown to reduce weight-related complications of subsequent pregnancies in adults, it is important to counsel adolescent females to avoid pregnancy during the period of rapid weight loss and up to 12-18 months after surgery.…”
Section: Nutritional Risks Of Weight Loss Surgerymentioning
confidence: 99%